Observed (1970-1999) climate variability in Central America using a high-resolution meteorological dataset with potential for climate change studies - Alfaro Martínez, Eric J. (2015)
Work presented also at: Observing & Modeling Climate Variability in the Intra-Americas Seas & Impacts on the Continental Americas and Caribbean (https://usclivar.org/meetings/2015-iasclip-virtual-workshop) and at: International Conference on Southern Hemisphere Meteorology and Oceanography, (11th, Santiago, Chile, October 5-9 2015).